Dampak Investasi Asing Langsung Terhadap Penyerapan Tenaga Kerja di ASEAN: Peran Kualitas Tenaga Kerja - Dwi Putri Lestari; Selli Nelonda (Media Riset Ekonomi Pembangunan (MedREP), 2026)
The mismatch between high inflows of Foreign Direct Investment (FDI) and uneven labor absorption across ASEAN countries is the main issue addressed in this study. Therefore, this research aims to analyze the effect of FDI on employment absorption and the role of labor quality as an interaction variable. This study uses panel data of ASEAN countries for the period 2014-2023 and applies panel data regression with a Fixed Effect Model (FEM)robust approach. The results show that FDI has a positive and significant effect on employment absorption, while labor quality has a positive but not significant effect. The interaction between FDI and labor quality has a negative and significant effect. In addition, inflation has no significant effect, urbanization has a negative and significant effect, and the labor force participation rate has a positive and significant effect on employment absorption. These findings indicate that the impact of FDI on employment absorption is not uniform and is influenced by labor quality and the economic structure of each country. Keywords: Foreign Direct Investment, Employment Absorption, Labor Quality